Catalytic conversion of greenhouse gases (CO2 and CH4) to syngas over Ni-based catalyst: Effects of Ce-La promoters - Farooqi, A.S. (Elsevier B.V., 2020)
Dry reforming of methane (DRM) is an emerging technology as it can simultaneously serve as a prospective alternative energy source and mitigate greenhouse gases (e.g. CH4 and CO2). However, the industrial applications of DRM remain restricted due to the poor prospect of catalyst deactivation. In this study, the effects of adding CeO2 and La2O3 as promoters on the catalytic performance of Ni/Al2O3 catalyst were assessed. Catalysts such as Ni/Al2O3, Ni/Al2O3-La2O3, and Ni/Al2O3-CeO2 were synthesized at nano level using the sol-gel method. Citric acid was added to improve the reactivity of catalysts before the application of DRM. Various characterisation techniques were used to characterise synthesized catalysts, including Brunauer-Emmett-Teller (BET) analysis, temperature-programmed reduction (TPR), field emission scanning microscopy (FESEM), X-ray diffraction (XRD), and transmission electron microscopy (TEM). The results revealed that the BET surface area of the synthesized catalyst slightly decreased when CeO2 and La2O3 were added due to the deposition on the porous structure of the support. Meanwhile, the XRD results demonstrated the increase in reducibility and dispersion of Ni using CeO2 promoter and the inhibited development of the non-active phase of Ni/Al2O3 using La2O3 promoter (i.e. NiAl2O4), resulting in the carbon formation and reduced efficiency of the catalyst. The catalytic performance in DRM at 800 Â°C showed that Ni/Al2O3-CeO2 catalyst exhibited higher catalytic performance in terms of CH4 and CO2 conversion with 89.6 and 91.2 respectively. While Ni/Al2O3-La2O3 was found to play a substantial role in the stability of the chemical reaction during the 8 h reaction time-on-stream. Â© 2020 The Author(s)